ANALISIS KEUNTUNGAN AGROINDUSTRI GULA AREN DI KELURAHAN PANDU, KECAMATAN BUNAKEN, KOTA MANADO - Marhaeny Ketty Derek; Rine ., Kaunang; Joachim N.K. Dumais (Sam Ratulangi University, 2017)
The objective of this research is to analyze the benefits received by the palm sugar household industry is in one time production process. This research was conducted in Pandu Village, Bunaken Subdistrict,Manado City. This study was conducted for 3 months from June to August 2017. The data obtained is the primary data obtained from three farmer craftsmen of palm sugar. Based on the result ofthe research, it can be concluded that the business of oil palm agroindustry in Pandu Urban Village, Bunaken Sub-district, Manado City is very profitable and get value R / C = 2, 29 which means theindustry is profitable and feasible to be developed.